2013
DOI: 10.13067/jkiecs.2013.8.9.1383
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Changes of Ankle Joint Position Sense and Sway Area Through Unstable Surface Training

Abstract: This research was conducted to see the correlation between changes of ankle Joint Position Sense and Sway Area through Unstable Surface training. For the study, 48 healthy males and females were randomly divided into an unstable surface group(n=24) and a stable surface group(n=24). Then, they were asked to carry out the same exercise program three times a week for six weeks. The unstable surface group and stable surface group performed the exercise program on the balance exercise pad and on the hard ground, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Lee 19 ) suggested that exercise on an aero step is an effective at enhancing muscle strength because it facilitates the somatosensory, vestibular and visual systems, related to maintaining the posture, without stressing the patients. Moreover, it was found in a previous study, that the muscle strengths of the ankle and knee joints were increased after exercise on an unstable surface 20 ) . Based on these results, we consider that exercise on an unstable surface has a positive effect on the body function and muscle strength of patients with osteoarthritis.…”
Section: Discussionmentioning
confidence: 88%
“…Lee 19 ) suggested that exercise on an aero step is an effective at enhancing muscle strength because it facilitates the somatosensory, vestibular and visual systems, related to maintaining the posture, without stressing the patients. Moreover, it was found in a previous study, that the muscle strengths of the ankle and knee joints were increased after exercise on an unstable surface 20 ) . Based on these results, we consider that exercise on an unstable surface has a positive effect on the body function and muscle strength of patients with osteoarthritis.…”
Section: Discussionmentioning
confidence: 88%
“…Generally, the ankle joint is pivotal for balance and postural control during standing and walking [11] and contributes to sensory feedback crucial for maintaining proper posture through the soles of the feet [12]. The gastrocnemius muscle (GCM) plays a vital role in maintaining balance by keeping the feet in close contact with the ground during walking [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ankle joints provide the most basic exercise strategies for balance and posture control when standing or walking. 1 In addition, ankle joint plays a key role in absorbing shock, supporting weight, and maintaining stability of legs during walking. 2 Causes of instability of the ankle joint include anatomical instability of the skeletal system, weakness of muscle strength, and insufficient proprioception.…”
Section: Introductionmentioning
confidence: 99%